Policosanol alleviates chronic stress-induced growth impairment via gut microbiota-metabolite interactions: insights from 16S rRNA sequencing and LC-MS metabolomics - Wang, Ruxia; Hu, Linfang; Tu, Yue; Zhai, Zhenya; Niu, Kaimin; Guo, Xiongchang; Cai, Lichuang; Liu, Jianping (Frontiers in Nutrition, 2026)
Background/objectivesPolicosanol, a bioactive compound derived from rice bran wax, has demonstrated potential for alleviating stress, yet its underlying mechanisms remain elusive. This study aimed to elucidate its role in mitigating chronic stress-induced growth impairment and to explore its interactions with the gut microbiota and metabolomics.MethodsMale rats were subjected to a 4-week chronic restraint stress protocol with or without policosanol supplementation (2 mg/kg/day). Systemic responses were evaluated by measuring growth parameters (including weight gain and muscle mass), serum biomarkers [cortisol and catecholamines (CA)], 16S rRNA sequencing (for cecal microbiota analysis), and LC-MS metabolomics (for cecal metabolite profiling).ResultsStress induced a significant reduction in weight gain (−11.0%, p < 0.05) and a marked elevation of serum cortisol (+86.2%) and CA (+88.3%, both p < 0.05). Policosanol treatment restored weight gain to 85.5% of control levels (p < 0.05) and reduced cortisol and catecholamine levels by 29.5% and 26.8%, respectively (both p < 0.05). Stress-induced alterations in gut microbiota included a 4.1-fold increase in p_Verrucomicrobiota and a 3.8-fold increase in g_Akkermansia, along with metabolite changes such as a 4.2-fold elevation in Proscillaridin and a 65% decrease in Phenylacetylglutamine (PAGln) (both p < 0.05). Policosanol supplementation normalized gut microbiota composition (p_Verrucomicrobiota decreased by 36%, p < 0.05) and restored metabolite levels (PAGln increased by 80%, p < 0.01). Negative correlations were observed between g_Akkermansia abundance and weight gain (p < 0.01), while PAGln positively correlated with growth (p < 0.05) and negatively correlated with GSH-Px (p < 0.001), cortisol (p < 0.001), and CA (p < 0.001). Moreover, the g_Bacteroides–PAGln axis exhibited a strong interaction (p < 0.001).ConclusionPolicosanol mitigates stress-induced growth impairment by modulating gut microbiota (e.g., reducing p_Verrucomicrobiota and g_Akkermansia abundances) and restoring metabolite levels (e.g., increasing PAGln). The coregulation of the gut microbiota and metabolome was highlighted by a strong correlation between g_Bacteroides and Phenylacetylglutamine (PAGln), suggesting a potential functional interaction that may contribute to the anti-stress effects of policosanol, though causality remains to be established.